2016
DOI: 10.2166/wst.2016.059
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced power production from microbial fuel cells with high cell density culture

Abstract: Improvement of power production in a microbial fuel cell (MFC) with a high cell density culture strategy was developed. By using high cell density culture, the voltage output and power density output of the MFC were enhanced about 0.6 and 1.6 times compared to the control, respectively. Further analysis showed that riboflavin concentration in the MFC was dramatically increased from 0.1 mg/L to 1.2 mg/L by high cell density culture. Moreover, the biofilm formation on the anode surface was significantly enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…4). Riboflavin concentrations in batch experiments that have been reported so far vary apparently depending on growth conditions between 30 and 450 nM (1719). Since we hypothesized that riboflavin could be a quorum sensing molecule that is used by the cells to initiate a cell concentration-dependent physiological response, we quantified the response of the speC promoter on the addition of riboflavin at concentrations between 0 and 100 nM.…”
Section: Resultsmentioning
confidence: 99%
“…4). Riboflavin concentrations in batch experiments that have been reported so far vary apparently depending on growth conditions between 30 and 450 nM (1719). Since we hypothesized that riboflavin could be a quorum sensing molecule that is used by the cells to initiate a cell concentration-dependent physiological response, we quantified the response of the speC promoter on the addition of riboflavin at concentrations between 0 and 100 nM.…”
Section: Resultsmentioning
confidence: 99%
“…The cell suspension in electrolyte was added into the anodic chamber, while the cathodic chamber was lled with 50 mM K 3 [Fe(CN) 6 ] and KCl solution. 24 The MFCs were operated at 30 C and pH 7.0 (maintained by the phosphate buffer in the electrolyte) 23 (Fig. S1 †).…”
Section: Mfc Set-up and Electrochemical Analysismentioning
confidence: 99%
“…Already in Marsili et al (2008) showed that riboflavin accumulates in the supernatant of 4-day-old biofilms in concentrations of 250 to 500 nM (Marsili et al, 2008). Other groups measured only 25 nM flavin in the bulk solution and a change of the BES setup resulted in a different concentration of riboflavin (Velasquez-Orta et al, 2010; Zhai et al, 2016; Lu et al, 2017). Independent of the natural concentration, the artificial addition of riboflavin has stimulatory effects in a BES and this seems to be linearly dependent on the riboflavin concentration in a certain concentration range.…”
Section: Introductionmentioning
confidence: 99%
“…Independent of the natural concentration, the artificial addition of riboflavin has stimulatory effects in a BES and this seems to be linearly dependent on the riboflavin concentration in a certain concentration range. Consequently, several groups tried to raise the riboflavin concentration either via genetic engineering of MR-1 itself or via co-culturing with other riboflavin producing strains (Zhai et al, 2016; Lu et al, 2017). Still, from an application point of view, although bioelectrochemical systems (BESs) are perfectly suited for continuous biofilm based biotechnological production, the constant stream of fresh media over the biofilm would result in a continuous wash out of flavin compounds.…”
Section: Introductionmentioning
confidence: 99%